2020
DOI: 10.3389/fimmu.2020.02182
|View full text |Cite
|
Sign up to set email alerts
|

Fasciola hepatica-Derived Molecules as Regulators of the Host Immune Response

Abstract: Helminths (worms) are one of the most successful organisms in nature given their ability to infect millions of humans and animals worldwide. Their success can be attributed to their ability to modulate the host immune response for their own benefit by releasing excretory-secretory (ES) products. Accordingly, ES products have been lauded as a potential source of immunomodulators/biotherapeutics for an array of inflammatory diseases. However, there is a significant lack of knowledge regarding the specific intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 97 publications
(126 reference statements)
1
31
0
1
Order By: Relevance
“…This could be considered to be the case during infection with F. hepatica, which is responsible for chronic infections in ruminants. As a consequence of a parasite-driven mixed Th1/Th2 response that then shifts to a Th2-type cytokine pattern devoid of the inflammatory component the parasite is able to reach its adult stage [28]. F. hepatica secretions have been widely studied in the last few years due to the application of the new -omics techniques [29].…”
Section: Resultsmentioning
confidence: 99%
“…This could be considered to be the case during infection with F. hepatica, which is responsible for chronic infections in ruminants. As a consequence of a parasite-driven mixed Th1/Th2 response that then shifts to a Th2-type cytokine pattern devoid of the inflammatory component the parasite is able to reach its adult stage [28]. F. hepatica secretions have been widely studied in the last few years due to the application of the new -omics techniques [29].…”
Section: Resultsmentioning
confidence: 99%
“…The best form of defence, however, is having a good offence, and helminth parasites achieve this largely by the excretion/secretion of a multitude of immune-impairing, -suppressive or -modulatory factors ( Hewitson et al., 2009 ; Ryan et al., 2020 ). In the case of F. hepatica , these include proteases, protease inhibitors, antioxidants, cathelicidin-like helminth defence molecules (HDM) and glycolytic enzymes ( Jefferies et al., 2001 ; Morphew et al., 2007 ; Ryan et al., 2020 ), many of which have been shown to influence different aspects of the host’s immune response.…”
Section: The Best Form Of Defence Is Having a Good Offencementioning
confidence: 99%
“…The best form of defence, however, is having a good offence, and helminth parasites achieve this largely by the excretion/secretion of a multitude of immune-impairing, -suppressive or -modulatory factors ( Hewitson et al., 2009 ; Ryan et al., 2020 ). In the case of F. hepatica , these include proteases, protease inhibitors, antioxidants, cathelicidin-like helminth defence molecules (HDM) and glycolytic enzymes ( Jefferies et al., 2001 ; Morphew et al., 2007 ; Ryan et al., 2020 ), many of which have been shown to influence different aspects of the host’s immune response. For example, early studies showed that secreted cysteine proteases (now known as cathepsin B and cathepsin L proteases) can specifically cleave immunoglobulins (Igs) at their hinge region, separating the antibody binding Fab fragment from the Fc domain and thus preventing the ability of bound Ig to attract Fc-binding innate immune cells (eosinophils, macrophages) ( Chapman and Mitchell, 1982 ).…”
Section: The Best Form Of Defence Is Having a Good Offencementioning
confidence: 99%
See 1 more Smart Citation
“…With the advancement in helminth genomics, studies on ES products have revealed a set of proteins secreted by helminths, including proteases, protease inhibitors, venom-allergen homologues, glycolytic enzymes and lectins [15]. The composition of these proteins has been characterised in Brugia malayi [16], Necator americanus [17], Toxocara canis [18], Ancylostoma caninum [19] and Fasciola hepatica [20]. However, knowledge of the possible virulence mechanisms involved during A. lumbricoides infection is limited.…”
Section: Introductionmentioning
confidence: 99%